The Effects of a Heel Wedge on Hip, Pelvis and Trunk Biomechanics During Squatting in Resistance Trained Individuals. Issue 6 (June 2017) - Charlton, Jesse M.; Hammond, Connor A.; Cochrane, Christopher K.; Hatfield, Gillian L.; Hunt, Michael A.
Abstract : Abstract: Charlton, JM, Hammond, CA, Cochrane, CK, Hatfield, GL, and Hunt, MA. The effects of a heel wedge on hip, pelvis, and trunk biomechanics during squatting in resistance trained individuals. J Strength Cond Res 31(6): 1678–1687, 2017—Barbell back squats are a popular exercise for developing lower extremity strength and power. However, this exercise has potential injury risks, particularly to the lumbar spine, pelvis, and hip joint. Previous literature suggests heel wedges as a means of favorably adjusting trunk and pelvis kinematics with the intention of reducing such injury risks. Yet no direct biomechanical research exists to support these recommendations. Therefore, the purpose of this study was to examine the effects of heel wedges compared with barefoot on minimally loaded barbell back squats. Fourteen trained male participants performed a barbell back squat in bare feet or with their feet raised bilaterally with a 2.5-cm wooden block while 3-dimensional kinematics, kinetics, and electromyograms were collected. The heel wedge condition elicited significantly less forward trunk flexion angles at peak knee flexion, and peak external hip joint moments ( p ⩽ 0.05) compared with barefoot conditions. However, no significant differences were observed between conditions for trunk and pelvis angle differences at peak knee flexion ( p > 0.05). Lastly, no peak or root mean square differences in muscle activity were elicited between conditions ( p > 0.05). Our results lend support for the suggestions provided in literature aimed at using heel wedges as a means of reducing excessive forward trunk flexion. However, the maintenance of a neutral spine, another important safety factor, is not affected by the use of heel wedges. Therefore, heel wedges may be a viable modification for reduction of excessive forward trunk flexion but not for reduction in relative trunk-pelvis flexion during barbell back squats.